Between Norm and Practice: Dynamics of Muhammadiyah Political Communications - Muhammad Nurul Yamin (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This study aims to describe the dynamics of Muhammadiyah political communication. The research is based on the background that Muhammadiyah is a civil society organization engaged in the socio-religious field in Indonesia and is non-political, but has political power. Muhammadiyah's political communication is studied within the framework of the theory of